2022
DOI: 10.1017/s0030605321001472
|View full text |Cite
|
Sign up to set email alerts
|

A before−after assessment of the response of mammals to tourism in a Brazilian national park

Abstract: Worldwide, nature-based tourism is becoming more popular and important economically. However, there is still debate regarding its impact on wildlife in protected areas. We conducted a quasi-experimental study to investigate the effects of tourism on the mammal community of Cavernas do Peruaçu National Park, a priority area for conservation in Brazil. We used camera traps to survey tourist and non-tourist trails during 2011–2017, encompassing periods before and after tourism started in the Park. We used four me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
2
0
1
Order By: Relevance
“…The assemblage responded positively to the distance to touristic sites, possibly as a general pattern in which the species avoid contact with humans due to negative interactions. This behavior has been reported in several studies, where mammals tend to avoid touristic roads or even change their occurrence pattern after touristic activities (Barcelos et al 2022; LI et al 2015). Regarding the human footprint, the association with assemblage occupancy was negative, a pattern that has been widely documented for mammals in different ecosystems around the world (Hill et al 2020; Nickel et al 2020; Thatte et al 2020; Toews 2016; Toews et al 2018).…”
Section: Discussionsupporting
confidence: 68%
“…The assemblage responded positively to the distance to touristic sites, possibly as a general pattern in which the species avoid contact with humans due to negative interactions. This behavior has been reported in several studies, where mammals tend to avoid touristic roads or even change their occurrence pattern after touristic activities (Barcelos et al 2022; LI et al 2015). Regarding the human footprint, the association with assemblage occupancy was negative, a pattern that has been widely documented for mammals in different ecosystems around the world (Hill et al 2020; Nickel et al 2020; Thatte et al 2020; Toews 2016; Toews et al 2018).…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, a study conducted by Barcelos et al (2022) investigated the effects of tourism on the mammal community of Cavernas do Peruacu National Park in Brazil using camera traps, found that tourist visitation had limited negative impacts for terrestrial species of mammals, in general, but specifically displaced one medium-sized rodent species and reduced the diurnal activity of ocelots, concluding that this was as an indication of temporal adjustment. This coincides with ocelots in our study site also showing a reduction in diurnal activity on experimental trails after the lockdown was lifted and tourist activity returned to the site.…”
Section: Wildlife Lettersmentioning
confidence: 98%
“…O crescimento urbano que ocorre sem planejamento ocasiona, comumente, problemas ambientais que impactam fortemente em quem reside ou faz uso das cidades. Nesse sentido, as alterações hidrológicas associadas ao processo de urbanização têm sido estudadas a partir da segunda metade do século XX, e os seus resultados têm mostrado que o desenvolvimento urbano e, a consequente ampliação da impermeabilização dos solos levam a inundações maiores e mais frequentes nas áreas de planícies fluviais ocupadas (CHIN, 2006;FERREIRA, 2022). -SNIRH e por fim um documento que garanta os direitos do uso e a cobrança por tal uso (BRASIL, 1997).…”
Section: Introductionunclassified